Impact of Breast Cancer in Women’s of Satna District, Madhya Pradesh - Sharma, U; Narain, B (International Journal of Computer Sciences and Engineering, 2025)
Dynamic data is a common challenge in digital Image processing. It has played an important role in modern and previous era in community. In past, masses were using the process of Images processing in photogenic devices such as cameras, but as time changes technology changes. The camera has been replaced by Mobile Camera which is one of the convent resources. As the technology does not remain same and has been changed so far by new thoughts and ideas as different image processing, techniques, equipment’s, is programming tools. In research various programming language tools are used for manipulation of images processing (advance java, Mat lab, Scilab, Opencv, Artificial Neural Network). Medical imaging plays an important role in clinical study such as (x-ray, Ultrasound, Mammography, Computed tenography (C.T.), Magnetic Resonance imaging (MRI) are getting popular. In this context we have used agent–based coordinate between medical and research institution. In this paper we have studied the approximation of Image processing and proficiency applied for medical Image processing in Madhya Pradesh (M.P), India. In the first segment of our paper; we have given introduction of Satna district in Madhya Pradesh, Percentage of cancer patients in Madhya Pradesh and how it is affecting the people of Satna and about cancer research center and education in Satna. In second segment we have discussed digital image processing, techniques, equipment’s and some related work used in breast cancer diagnosis. In the third segment; we involve recent tools which are used for breast cancer diagnosis. Forth segment we have given list of observation that we have seen in the hospitals during our visit. In fifth segment conclusion of our work has been draw